2019
DOI: 10.1002/edm2.104
|View full text |Cite
|
Sign up to set email alerts
|

Serum C‐peptide and osteocalcin levels in children with recently diagnosed diabetes

Abstract: Background:We explored the association of C-peptide (marker of secreted insulin), proinsulin and proinsulin ⁄C-peptide ratio (PI/C) (markers of beta-cell endoplasmic reticulum [ER] stress) with undercarboxylated (uOC) and carboxylated osteocalcin (cOC) and their ratio (uOC/cOC) in children with recently diagnosed type 1 (T1D) or type 2 diabetes (T2D), and the correlation of these variables with partial remission (PR) in children with T1D.Methods: Demographic and clinical data of children with new-onset diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…The consistent finding that insulin-signaling in osteoblastic cells is involved in ucOC physiology, is also supported by findings from human studies. We and others have demonstrated that in humans with type 1 diabetes, a condition of insulin deficiency, serum concentrations of ucOC are positively associated with insulin exposure, either exogenously administered or endogenously produced, as assessed by c-peptide levels 11,12 . Because this www.nature.com/scientificreports www.nature.com/scientificreports/ association holds true from shortly after the diagnosis of type 1 diabetes to many years after the diagnosis, some have proposed the ucOC might be a useful surrogate marker for residual β-cell function in type 1 diabetes 12 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The consistent finding that insulin-signaling in osteoblastic cells is involved in ucOC physiology, is also supported by findings from human studies. We and others have demonstrated that in humans with type 1 diabetes, a condition of insulin deficiency, serum concentrations of ucOC are positively associated with insulin exposure, either exogenously administered or endogenously produced, as assessed by c-peptide levels 11,12 . Because this www.nature.com/scientificreports www.nature.com/scientificreports/ association holds true from shortly after the diagnosis of type 1 diabetes to many years after the diagnosis, some have proposed the ucOC might be a useful surrogate marker for residual β-cell function in type 1 diabetes 12 .…”
Section: Discussionmentioning
confidence: 93%
“…We and others have demonstrated that in humans with type 1 diabetes, a condition of insulin deficiency, serum concentrations of ucOC are positively associated with insulin exposure, either exogenously administered or endogenously produced, as assessed by c-peptide levels 11,12 . Because this www.nature.com/scientificreports www.nature.com/scientificreports/ association holds true from shortly after the diagnosis of type 1 diabetes to many years after the diagnosis, some have proposed the ucOC might be a useful surrogate marker for residual β-cell function in type 1 diabetes 12 . Post-hoc analyses examining correlations between fasting insulin levels and ucOC (R 2 = −0.259; p = 0.02) or cOC (R 2 = −0.363; p = 0.005) in control and postnatal OIRKO mice demonstrates an inverse correlation between fasting insulin levels and ucOC and cOC, suggesting that insulin signaling in osteoprogenitors regulates the production of ucOC and cOC.…”
Section: Discussionmentioning
confidence: 93%
“…BMI was significantly correlated to fasting C-peptide in both the Swedish and the Finnish participants, while BMI was significantly correlated to fasting insulin in the Swedish participants only and to fasting glucose in the Finnish participants. It has previously been shown that there is a correlation between BMI and C-peptide in healthy children 12 as well as in patients newly diagnosed with type 1 diabetes, both in paediatric cases 13 and in adult cases. 14 The correlation between BMI and insulin in the Swedish participants, but BMI and glucose in the Finnish participants, is difficult to explain.…”
Section: Discussionmentioning
confidence: 98%
“…In a clinical trial involving 75 middle-aged to aged Japanese without any anti-diabetic agent administration, it was observed that ucOCN is correlated with HbA1c and insulinogenic index (IGI) in the DM group, and ucOCN plays more vital roles in insulin secretion than in insulin sensitivity in patients with DM ( 75 ). In a study of children with newly diagnosed DM, serum C-peptide levels are related to a higher ucOCN and ucOCN/cOCN ratio ( 76 ). The abovementioned research suggested OCN favors insulin secretion in patients with DM, but the relationship between OCN and glucose homeostasis, which is crucial for controlling the progression of DM complications, is uncertain.…”
Section: Bone-derived Hormones and Dkdmentioning
confidence: 99%